Mediating role of psychological resilience between depression and humoral immunological biomarkers in medical staff - Yunyun MA; Yanshuan WEI; Lili QIAN; Xiufeng ZUO; Dechao WANG; Shanfa YU (环境与职业医学)
BackgroundAt present, high level of depression is a serious problem in medical staff and may affect their immune function. The role of psychological resilience between depression and immunity cannot be ignored. However, it is still lack of research report in this area. ObjectiveTo explore the mediating effect of psychological resilience on the association between depression and humoral immunological biomarkers in medical staff. MethodsA total of 108 medical staff from a tertiary hospital in Henan Province were selected using stratified cluster sampling from September 2022 to December 2022. The Connor-Davidson Resilience Scale and Patient Health Questionnaire-9 were used to evaluate their psychological resilience and depression. Serum immunoglobulin (Ig) M (IgM), IgG, IgA, complement 3 (C3), and complement 4 (C4) were detected in fasting venous blood samples. Mann-Whitney U test, Kruskal-Wallis H test, independent-samples t-test, and One-way ANOVA were used for comparisons among different demographic groups. Spearman correlation was used to evaluate correlations among measured variables. PROCESS plug-in was used to verify potential mediating effect of psychological resilience on the relationship between depression and humoral immunological biomarkers. ResultsThe M (P25, P75) score of psychological resilience was 65.50 (53.25, 75.00) in the participating medical staff. The ratios of low, medium, and high levels of psychological resilience were 2.78% (3/108), 51.85% (56/108), and 45.37% (49/108), respectively. The M (P25, P75) score of depression was 6.00 (2.00, 8.00). The positive rate of depression was 61.11% (66/108). The correlation analysis results showed that psychological resilience was negatively correlated with depression and serum complement C3 (r=−0.416 and −0.309, P＜0.01), positively correlated with serum IgG and serum IgA (r=0.302 and 0.517, P＜0.01); optimism, self-improvement, and resilience were negatively correlated with depression (r=−0.387, −0.446, and −0.312, P<0.01), positively correlated with IgG (r=0.194, 0.284, and 0.239, P<0.05), and positively correlated with IgA (r=0.377, 0.378, and 0.444, P<0.01), respectively; resilience was negatively correlated with C3 (r=−0.304, P<0.01), and depression was negatively correlated with serum IgG and serum IgA (r=−0.516 and −0.522, P＜0.01), positively correlated with serum complement C3 (r=0.195, P＜0.05). The mediating effect test showed that psychological resilience showed mediating effects on the relationship between depression and serum IgA and serum complement C3, with mediating effect values of −0.148 (95%CI: −0.051, −0.012) and 0.111 (95%CI: 0.001, 0.010), and their mediating effect ratios were 28.30% and 56.92%. ConclusionThe mental health status of the target medical staff is not optimistic. Depression is associated with changes in some humoral immunological biomarkers. Psychological resilience can mediate the correlations between depression and humoral immunological biomarkers. The managers should take measures to improve the levels of psychological resilience and promote the physical and mental health of medical staff.